Advanced prehospital resuscitative care: Can we identify trauma patients who might benefit?. Issue 3 (September 2021) - Irfan, Ahmer; Juneja, Kavina; Abraham, Peter; Smedley, W. Andrew; Stephens, Shannon W.; Griffin, Russell L.; Ward, William; Hallmark, Robert; Qasim, Zaffer; Carroll, Shannon L.; Reiff, Donald; Holcomb, John B.; et al.
Abstract : BACKGROUND: Uncontrolled truncal hemorrhage remains the most common cause of potentially preventable death after injury. The notion of earlier hemorrhage control and blood product resuscitation is therefore attractive. Some systems have successfully implemented prehospital advanced resuscitative care (ARC) teams. Early identification of patients is key and is reliant on rapid decision making and communication. The purpose of this simulation study was to explore the feasibility of early identification of patients who might benefit from ARC in a typical US setting. METHODS: We conducted a prospective observational/simulation study at a level I trauma center and two associated emergency medical service (EMS) agencies over a 9-month period. The participating EMS agencies were asked to identify actual patients who might benefit from the activation of a hypothetical trauma center-based ARC team. This decision was then communicated in real time to the study team. RESULTS: Sixty-three patients were determined to require activation. The number of activations per month ranged from 2 to 15. The highest incidence of calls occurred between 4 PM to midnight. Of the 63 patients, 33 were transported to the trauma center. The most common presentation was with penetrating trauma. The median age was 27 years (interquartile range, 24–45 years), 75% were male, and the median Injury Severity Score was 11 (interquartile range, 7–20). Based on injury patterns, treatment received, and outcomes, it was determined that 6 (18%) of 33 patients might have benefited from ARC. Three of the patients died en-route to or soon after arrival at the trauma center. CONCLUSION: The prehospital identification of patients who might benefit from ARC is possible but faces challenges. Identifying strategies to adapt existing processes may allow better utilization of the existing infrastructure and should be a focus of future efforts. LEVEL OF EVIDENCE: Prognostic/Epidemiologic, level III.